Exploring the Use of Digital Media Platforms for Social Change in Teaching Hospitals in Rivers State - Joy Collins-Dike; Dike Harcourt White; Njoku C. Justice; Richard N. Amadi; Muhammad Ridwan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This study examined the utilization of digital media platforms for social change initiatives within teaching hospitals in Rivers State, Nigeria, focusing on University of Port Harcourt Teaching Hospital and Rivers State University Teaching Hospital. The objectives were to identify the digital media platforms employed, explore the specific strategies used to promote health awareness and patient engagement, evaluate the impact of digital media on healthcare communication and community outreach, and analyze the challenges encountered in leveraging these platforms for social change. Grounded in the social network theory, diffusion innovations theory and technology acceptance model (TAM). The study used a mixed-methods approach, including a structured questionnaire with 384 respondents and in-depth interviews with hospital staff. Findings indicate that widely used platforms include Facebook, WhatsApp, and hospital websites, chosen for their accessibility and broad reach. Digital media strategies primarily focus on information dissemination, health awareness campaigns, and interactive engagement with patients. The study finds that digital media positively impacts healthcare communication by enabling faster information sharing, improving patient engagement, and facilitating community outreach. However, barriers such as poor internet connectivity, privacy concerns, and limited digital literacy hinder the effectiveness of these platforms. Recommendations emphasize the need for improved infrastructure, digital literacy training, and enhanced management support to maximize the benefits of digital media in healthcare. This study contributes to the field by providing insights into digital media's role in healthcare within a resource-limited setting, with implications for enhancing health communication and patient-centered care in similar contexts.